Predicting gradient mechanical behaviour of a shot-peened structure. (1st February 2023) - Zhou, Jianqiang; Xu, Xiangdu; Sun, Zhidan; Retraint, Delphine; Zhang, Xianjie; Xue, Hongqian
Highlights: Early yielding and strengthening occur for SMATed specimen under tensile test. Residual work hardening is reconstructed considering the scalar and tensor features. Developed constitutive model is used to well predict early yielding and strengthening. Residual stress release is strongly related to the residual work hardening gradient. Local yield strength in plastically affected region may not be improved due to SMAT. Abstract: Gradient features including stress–strain response, yield strength, and hardening behaviour of a shot-peened structure is studied under uniaxial tension by modelling residual stress field and residual work hardening (RWH). Three representative constitutive models are used in predicting the tensile behaviour of the shot-peened structure, with the RWH being considered in different ways. The experimentally observed early yielding and strengthening effect of the shot-peened structure can be well predicted by the reconstructed RWH gradient coupled with a developed combined isotropic/kinematic hardening (Developed-CIK) model. Analyses show that the shot peening does not obviously increase yield strength of the material in each layer, but improves the resistance to plastic deformation through increasing the kinematic hardening level. This is contradictory to the general opinion that the yield strength can be improved due to shot peening. Further discussion indicates that an accurate characterization of the RWH and a thorough consideration in an appropriate constitutive model are crucial to precisely predict mechanical properties of a shot-peened structure and residual stress release during a certain loading.